Penguatan Karakter pada Remaja Melalui Teknik Assertive Training pada PKL 1 di Panti Asuhan Ora Et Labora - Annisa Amanda Putri; Fajar Utama Ritonga (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
This paper aims to Strengthen the Character of adolescents through Assertive Training Techniques on assertive behavior owned by orphanage youth who are unable to express their emotions and opinions through Field Work Practices (PKL). The purpose of this street vendor is to carry out a Mini Project by applying the casework method in solving client problems. The method used in this research is descriptive qualitative with a case study approach. Based on the results of observations made on one of the orphanages who were used as clients, it can be seen that the client has difficulty expressing his emotions and opinions, the child cannot refuse his friend's invitation to do negative things because he is afraid of what his friends will think. Based on this, it was identified that the client had problems with controlling emotions (aggressive) and found it difficult to express or convey his thoughts (non-assertive). Through the Assertive Training Technique as a character strengthening method which was carried out several times during the street vendors, there was quite good progress, namely, the client began to be able to apply assertive behavior in everyday life and as a result he became more confident in expressing his feelings and not easily influenced by the environment and his friends.